2022
DOI: 10.3390/diagnostics12123105
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Dysgerminomas with a Brief Summary of Primitive Germ Cell Tumors

Abstract: Dysgerminoma represents a rare malignant tumor composed of germ cells, originally from the embryonic gonads. Regarding its incidence, we do not have precise data due to its rarity. Dysgerminoma occurs at a fertile age. The preferred treatment is the surgical removal of the tumor succeeded by the preservation of fertility. Even if a multidisciplinary team, founded in 2009 by a gynecologist, an oncologist, a pediatric oncologist and a pediatric surgeon, under the guidance of the Malignant Germ Cell International… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Artificial intelligence technology delivers precise and sensitive image analysis results, greatly benefiting breast cancer management. Currently, many studies have applied AI in various aspects of breast cancer and even other cancers' management [33][34][35], including digital pathology [36], clinical prognosis, and biopsy result analysis, among others. It is worth mentioning that although the imaging source used in this study is based on DBT images of breast cancer tumor tissues, the principle of determining margins is not unique to breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence technology delivers precise and sensitive image analysis results, greatly benefiting breast cancer management. Currently, many studies have applied AI in various aspects of breast cancer and even other cancers' management [33][34][35], including digital pathology [36], clinical prognosis, and biopsy result analysis, among others. It is worth mentioning that although the imaging source used in this study is based on DBT images of breast cancer tumor tissues, the principle of determining margins is not unique to breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the accuracy of the MOGCT diagnosis remains unknown. While chemosensitivity and survival outcomes differ among dysgerminomas, YST, and immature teratomas, the current systematic review does not have enough information to examine the outcome of interest according to the histological subtypes of MOGCT [ 40 , 41 , 42 , 43 , 44 ]. Sixth, the meta-analysis may have limited value owing to the small number of published articles.…”
Section: Discussionmentioning
confidence: 99%
“…The literature also shows an association of clear cervical cell carcinoma (CCC) and cervical endometriosis [64]. According to an epidemiological study to analyze the association between the two diseases, it was observed that the low risk of cervical cancer decreased in women with cervical endometriosis [65].…”
Section: Discussionmentioning
confidence: 99%